Метафоризація як шлях творення семантики локусів на позначення віртуального простору сну - Лутава, Світлана; Lutava, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті з’ясовано та проаналізовано причини метафоричності й різноманітності лексем на позначення віртуального простору сну в художньому стилі сучасної української літературної мови, специфічні саме для цих номінацій; досліджено семантичні процеси метафоризації в номінаціях просторових об’єктів оніричної віртуальності на прикладах із художніх українськомовних текстів; виявлено специфіку основних напрямків метафоризації в цій лексиці, семантика якої залежить від характеру твору і художнього задуму, мети та стилю автора: зв’язок з українською традиційною народною культурою та національними архетипами, символікою може бути більш виражений або лише частково (паралельно з художніми переосмисленнями) чи й зовсім відсутній (на користь художності); встановлено продуктивність метафори як виду семантичної деривації в цьому виді локусів, окреслено перспективи подальшого вивчення семантичних процесів цієї групи слів в українській семасіології. The problem of studying the loci of irreality (nominations for the designation of place and space) is a hotly discussed issue in modern linguistics. However, few investigations have focused on highlighting the problem of the dream virtual space actualization in modern Ukrainian literary language. The lexicographic sources of the Ukrainian language and artistic texts served as the basis for the analysis. The study used the method of contextual analysis to determine the semantic structure of loci to describe the virtual space of sleep; a comparative analysis for the establishment of differential characteristics of productive nominations and a method of sem analysis for the determination of an integral (archetypal) sem. The article clarifies and analyzes the causes of metaphoric nature and diversity of the specific lexemes to designate the virtual space of sleep in the belle-letters style of the contemporary Ukrainian literary language. In the focus of the study are the semantic processes of metaphorization in the nominations of spatial objects of sleep virtuality on the examples from the artistic Ukrainian language texts. The research of these nominations in the artistic texts testifies the high efficiency of the semantic derivation. The emphasis is laid on the specificity of the main directions of metaphorization in this vocabulary stratum, the semantics of which depends on the content of the work, the artistic design or the purpose and style of the author. Relationship with the traditional Ukrainian folk culture and national archetypes and symbols can be more pronounced or only partial (in parallel with the artistic rethinking) or completely absent (in favor of the artistic vividness). The key findings of this study elucidate productivity of the metaphor as a form of semantic derivation in this type of locus and advocate further research of the semantic processes of this group of words in the Ukrainian semasiology.
Metaphorization as a Means of Creating Semantic Fields of the Loci on the Denomination of the Virtual Space of Sleep
Keywords: метафоризація; лексична семантика; локус; оніричний віртуальний простір; metaphorization; lexical semantics; locus; sleep virtual space